84.1k views
4 votes
Hi, I have utterly no idea what I'm doing here.

f(x)=9x3+2x2−5x+4 and g(x)+5x3−7x+4. what is f(x)−g(x)?
Show all of your steps and write your final answer in factored form.

I am so utterly confused right now. Help.

User DanielVest
by
4.4k points

2 Answers

7 votes

Answer:

2x(4x^2+x+1)

Explanation:

f(x) = 9x^3 + 2x^2 - 5x + 4

g(x) = 5x^3 +0x^2 - 7x + 4

f(x) - g(x) =

=(9x^3-5x^3) + (2x^2-0x^2) + (-5x - (-7x)) + (4-4) = 4x^3 +2x^2 +2x

=2x(4x^2+x+1)

User Shumii
by
4.7k points
4 votes

Answer:

Factored form: 2x(2x^2+x+1)

Explanation:

You're subtracting them. :)

User Alykoshin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.